Models of the fault-tolerant systems, build from the same type of modules with sliding and general redundancy - Volochiy, Bohdan; Ozirkovskyy, Leonid; Mulyak, Oleksandr; Gyla, Vasyl (Видавництво Львівської політехніки, 2010)
Fault-tolerant system with combined structural redundancy is used in the design of the server node memory and an uninterruptible power supply system of very important purposes. Suggested reliable models of such devices have a high degree of adequacy and allows to solve problems which contains multiple choice analysis with acceptable to the designer time expense.
Keywords: reliability; fault-tolerant system; combined structural redundancy; reliable design